2019
DOI: 10.3390/biom9120805
|View full text |Cite
|
Sign up to set email alerts
|

CSN5A Subunit of COP9 Signalosome Temporally Buffers Response to Heat in Arabidopsis

Abstract: The COP9 (constitutive photomorphogenesis 9) signalosome (CSN) is an evolutionarily conserved protein complex which regulates various growth and developmental processes. However, the role of CSN during environmental stress is largely unknown. Using Arabidopsis as model organism, we used CSN hypomorphic mutants to study the role of the CSN in plant responses to environmental stress and found that heat stress specifically enhanced the growth of csn5a-1 but not the growth of other hypomorphic photomorphogenesis m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…In the leaf epidermal cells of Arabidopsis, a strong correlation exists between the size of the cell and the amount of DNA (Melaragno et al, 1993). Plant cells frequently undergo endoreduplication, resulting in higher ploidy per nucleus which is correlated with increased cell size as well (Sugimoto- Shirasu and Roberts, 2003; Singh et al, 2019). As a result, the individual cell size and their numbers significantly contribute to the overall leaf size (Tsukaya, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…In the leaf epidermal cells of Arabidopsis, a strong correlation exists between the size of the cell and the amount of DNA (Melaragno et al, 1993). Plant cells frequently undergo endoreduplication, resulting in higher ploidy per nucleus which is correlated with increased cell size as well (Sugimoto- Shirasu and Roberts, 2003; Singh et al, 2019). As a result, the individual cell size and their numbers significantly contribute to the overall leaf size (Tsukaya, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic plants were generated by the floral‐dipping method (Clough & Bent, 1998). SAV4pro::SAV4‐YFP , PIN2pro::PIN2‐Venus , PIN2pro::PIN2‐GFP , DR5::N7‐Venus and 35S::EIN3‐GFP were previously reported (He et al ., 2011; Leitner et al ., 2012; Ge et al ., 2017; Singh et al ., 2019; Wang et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown which CSN is triggered by heat stress that disrupts the redox balance of rice . However, in Arabidopsis, the underlying mechanism of CSN in response to high temperatures has been reported to target auxin signaling, which drives plant growth and morphogenesis . A large body of evidence on the function of CSN in response to auxin may support this view.…”
Section: Influence Of Csn In High-temperature Stress and Auxin Signalingmentioning
confidence: 99%
“…Plants exhibit limited growth and productivity under abiotic stresses, such as excess salt and alkali, extreme temperatures, drought, excessive ultraviolet (UV) light irradiation, and nutrient deprivation. To respond and adapt to these adverse environmental conditions, plants adjust their physiology and activate the stress signaling pathway . Recently, a growing body of literature has reported the regulatory role of CSN in plants under abiotic stress. , The metabolic pathways of CSN in response to abiotic stress involve oxygen ion conduction, osmotic regulation, and signal transduction.…”
Section: Introductionmentioning
confidence: 99%